A Framework for Investigation of Soil Suffusion and Soil-Structure Interaction Effects on Seismic Performance of Prestressed Concrete Bridge - Imtiyaz Akbar, Najar (UNIMAS, 2025)
The interaction between soil and structures, termed soil-structure interaction (SSI), significantly influences structural behaviour during seismic events. This study develops a comprehensive framework to investigate soil suffusion and SSI's effects on the seismic behaviour of prestressed concrete bridges. Phase I involves case study selection, data collection, and software selection. Phase II focuses on field investigations, including electrical resistivity tomography (ERT) and standard penetration testing (SPT), and laboratory determination of key geotechnical parameters. Phase III investigates soil instability through ERT and hydraulic conductivity correlations, and evaluates suffusion susceptibility using empirical and experimental approaches. In Phase IV, the stability of the abutment slope under combined seismic and seepage effects is analysed using finite element modelling (FEM), revealing an initial factor of safety of 0.96, which improves to stability after geotextile gabion mattress reinforcement. Phase V examines SSI through FEM. Eight scaled ground motions are applied in response-history analyses. Findings reveal significant differences in amplification ratios between soil types, with type A exhibiting lower amplification than types D and E. SSI's kinematic effects and discrepancies between discrete and continuum models are highlighted, particularly in base shear, drift, and spectral acceleration responses. The research delivers correlations between soil resistivity and geotechnical parameters, provides insights into suffusion mechanisms, and establishes fragility curves for seismic performance. These contributions advance the understanding of SSI effects, improve seismic design guidelines, and enhance the resilience of bridges in seismic-prone regions.